2007
DOI: 10.1590/s1516-635x2007000300007
|View full text |Cite
|
Sign up to set email alerts
|

Performance and carcass characteristics of broiler chickens with different growth potential and submitted to heat stress

Abstract: In order to evaluate the effects of broiler genotype and of heat exposure on performance, carcass characteristics, and protein and fat accretion, six hundred one-day-old male broilers were randomly assigned in a 2 x 3 factorial arrangement, according to the following factors: genetic group (selected and non-selected broilers) and pair-feeding scheme (Ad32 - reared under heat stress and fed ad libitum; Ad23 - reared at thermoneutrality and fed ad libitum; Pf23 - reared at thermoneutrality and pair fed with Ad32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 22 publications
4
27
2
3
Order By: Relevance
“…However, the GRW (%) was higher in quails kept under ceramic roof compared to those kept under the fiber cement roof. This result is in agreement with those of studies with broiler chickens, in which the authors reported a reduction in the GRW (%) of birds kept at higher temperatures as an adaptation to reduce endogenous heat production (OLIVEIRA NETO et al, 2000;OLIVEIRA et al, 2006;ROSA et al, 2007).…”
Section: )supporting
confidence: 92%
“…However, the GRW (%) was higher in quails kept under ceramic roof compared to those kept under the fiber cement roof. This result is in agreement with those of studies with broiler chickens, in which the authors reported a reduction in the GRW (%) of birds kept at higher temperatures as an adaptation to reduce endogenous heat production (OLIVEIRA NETO et al, 2000;OLIVEIRA et al, 2006;ROSA et al, 2007).…”
Section: )supporting
confidence: 92%
“…Although under natural conditions the ambient temperature is not constant, the majority of the studies on the effects of heat stress on the performance and physiological responses of birds were conducted at high constant temperatures (OLIVEIRA NETO et al, 2000;OLIVEIRA et al, 2006aOLIVEIRA et al, , 2006bROSA et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, this was not the case, which suggested that for physiological adaptation, there was no need to reduce the relative weight of these organs; the results were different from those obtained with broilers (ROSA et al, 2007;OLIVEIRA NETO et al, 2000). Rosa et al (2007) observed a decrease in the relative weights of the heart and liver in broiler chickens (42 days of age) kept under heat stress (32 °C), compared with those kept at thermoneutral conditions (23 °C). These authors linked the reduction in maintenance requirements to the decrease in mass of the internal organs and the lower metabolic activity of these organs in the birds kept at 32 °C.…”
mentioning
confidence: 80%
“…Studies with broilers demonstrated that high temperatures (32 °C) induce a reduction in the size of the most metabolically active organs, in order to reduce the production of body heat, which results in increased carcass ratio:weight after fasting, and consequently, the increase of the carcass yield (OBA et al, 2012;ROSA et al, 2007); however, these changes were not evident in meat quails at 28 or 42 days of age.…”
mentioning
confidence: 99%
See 1 more Smart Citation